Youth violence assessment instruments: are they sensitive to change and are changes related to recidivism? - Koh, Li Lian (Psychology, crime & law, 2022)
Instruments designed to appraise the risk of young people acting violently are sometimes used to measure changes in risk over the course of treatment. This study examined measurement error, reliable change and the relationship between change and recidivism of three youth violence assessment instruments, the SAVRY, VRS-YV and SAPROF-YV. Each instrument was retrospectively rated from file data pertaining to the pre- and post-treatment assessments of 90 male adolescents who completed a violent offender treatment program. Group-level changes were observed for the total scores of all three tools, with the scores on the SAVRY showing the most reliable change. However, change scores derived from the three instruments was unrelated to reoffending. Further research is needed to better understand the relationship between change scores on these multi-item risk assessment measures and recidivism.